Bacterial Composition and Diversity of the Digestive Tract of Odontomachus monticola Emery and Ectomomyrmex javanus Mayr - Zhou Zheng; Xin Hu; Yang Xu; Cong Wei; Hong He (Insects, 2021)
Ponerine ants are generalist predators feeding on a variety of small arthropods, annelids, and isopods; however, knowledge of their bacterial communities is rather limited. This study investigated the bacterial composition and diversity in the digestive tract (different gut sections and the infrabuccal pockets (IBPs)) of two ponerine ant species (Odontomachus monticola Emery and Ectomomyrmex javanus Mayr) distributed in northwestern China using high-throughput sequencing. We found that several dominant bacteria that exist in other predatory ants were also detected in these two ponerine ant species, including Wolbachia, Mesoplasma, and Spiroplasma. Bacterial communities of these two ant species were differed significantly from each other, and significant differences were also observed across their colonies, showing distinctive inter-colony characteristics. Moreover, bacterial communities between the gut sections (crops, midguts, and hindguts) of workers were highly similar within colony, but they were clearly different from those in IBPs. Further, bacterial communities in the larvae of O. monticola were similar to those in the IBPs of workers, but significantly different from those in gut sections. We presume that the bacterial composition and diversity in ponerine ants are related to their social behavior and feeding habits, and bacterial communities in the IBPs may play a potential role in their social life.